Synagogue paintings as indicating a!developing conception of national redemption - Zvi Orgad (Images)
Abstract. Orgad Zvi, Synagogue paintings as indicating a developing conception of national redemption. “Images” vol. XXV, no. 34. Poznań 2019. Adam Mickiewicz University Press. Pp. 15–27. ISSN 1731-450X. DOI 10.14746/i.2019.34.01.